LEGAL CERTAINTY OF EXECUTION DECISION OF THE INDONESIAN NATIONAL ARBITRATION BOARD NUMBER: 14/VII/ARB/BANI-MDN/2019 - Bangun Simbolon; Ramlani Lina Sinaulan; Maryano (Scholar Express Journals, 2022)
The Arbitration Award is final and binding, meaning that the decision cannot be requested for legal remedies such as appeals and cassations and the decision is binding for the parties to be obeyed voluntarily. However, as in the Arbitration Award Decision Number: 14/VII/ARB/BANI-Mdn/2019 there is a very interesting legal issue to discuss where the application for execution is submitted not based on where the domicile of the Respondent is. In this study, the method used is empirical juridical which aims to find out and understand the power of execution of the Decision of the Indonesian National Arbitration Board Number: 14/VII/ARB/BANI-Mdn/2019 through the Bandung District Court
Keywords: Implementation Execution; Decision of the Indonesian National Arbitration Board